Linux For You (with CD & DVD) (Monthly) (EFY EnterpriesPvt. Ltd. New Delhi, 2010)
vol.50 Issue no.1 jan'2010 vol.50 Issue no.1 jan'2010 vol.50 Issue no.1 jan'2010 vol.50 Issue no.1 jan'2010 vol.50 Issue no.1 jan'2010
Keywords: Computer Science/ Information Science/ MCA/ M Tech CSE